POETIC TROPES AS ELEMENTS THAT ENHANCE AND DEEPEN THE LINGUISTIC WORLDVIEW OF THE SPEAKER (E Global Congress, 2024)
This article explores the role of poetic tropes in enhancing and deepening the linguistic worldview of speakers, illustrating how these elements contribute to a richer, more nuanced understanding of language and reality.